Structure and interfacial tension of a hard-rod fluid in planar confinement - brumby,PE; wensink,HH; haslam,AJ; Jackson,G (Langmuir, 2017)
The structural properties and interfacial tension of a fluid of hard-spherocylinder rod-like particles in contact with hard structureless flat walls are studied by means of Monte Carlo simulation. The calculated surface tension between the rod fluid and the substrate is characterized by a non-monotonic trend as a function of bulk concentration (density) over the range of isotropic bulk concentrations. As suggested by earlier theoretical studies, a surface-ordering scenario can be confirmed from our simulations: the local orientational order close to the wall changes from uniaxial to biaxial nematic when the bulk concentration reaches about 85% of the value at the onset of the isotropic-nematic phase transition. The surface ordering coincides with a wetting transition whereby the hard wall is wetted by a nematic film. Accurate values of the fluid-solid surface tension, the adsorption, and the average particle-wall contact distance are reported (over a broad range of densities into the dense nematic region for the first time), which may serve as a useful benchmark for future theoretical and experimental studies on confined rod fluids. The simulation data are supplemented with predictions from a second-virial density functional theory, which are in good qualitative agreement with the simulation results.